THU0162 LIKELIHOOD OF CLINICAL WORSENING AMONG RHEUMATOID ARTHRITIS PATIENTS WHO ACHIEVED A PARTIAL RESPONSE TO ADALIMUMAB AND WERE SUBSEQUENTLY SWITCHED TO SARILUMAB. (2nd June 2020) - Curtis, J.; Aletaha, D.; Burmester, G. R.; Ford, K.; Van Hoogstraten, H.; Leher, H.; Thangavelu, K.; Bykerk, V.
Abstract : Background: Rheumatoid arthritis (RA) patients who achieve a response to therapy but fail to reach low disease activity (LDA) or remission (partial responders) may decline treatment changes for fear of clinical worsening and losing their achieved response. Little is known about the likelihood of worsening after switching therapy in partial responders, and this limits patients' ability to make informed treatment decisions. Objectives: This post hoc analysis of the open-label extension (OLE) of MONARCH (NCT02332590 ) assesses the effects of switching from adalimumab to sarilumab in patients with RA who achieved a partial response to adalimumab but not remission or LDA. Methods: MONARCH was a 24-week, head-to-head monotherapy trial comparing sarilumab with adalimumab. At study end, patients randomized to adalimumab were switched to sarilumab 200 mg q2w for the OLE. Partial responders to adalimumab were defined as patients who had improved more than the minimal clinically important difference (MCID) in the Clinical Disease Activity Index (CDAI) during MONARCH, but who continued to have moderate to high disease activity (CDAI >10) at OLE baseline (BL). MCID was defined as a CDAI decrease ≥12 from a BL CDAI >22 or ≥6 from a BL CDAI >10 to ≤22. Response following treatment switch was assessed by change in CDAI and other outcomes from OLE BL to OLE Week 24. The effect of switching was analyzed descriptively and categorized: worsening = CDAI increase ≥6; improvement = CDAI decrease ≥6; stable = CDAI absolute change <6. Patients randomized to sarilumab in MONARCH continued to receive sarilumab in the OLE and were included as a control group. Results: Of 369 patients enrolled in MONARCH, 320 (87%) entered the OLE; 155 were switched from adalimumab to sarilumab, and of these, 91 were partial responders, who had a mean (SE) CDAI at OLE BL of 19.56 (0.86). Mean (SE) improvement in CDAI from OLE BL to OLE Week 24 in these patients was 7.37 (1.10). At OLE Week 24, only 6% of adalimumab partial responders had worsened after switching to sarilumab, while 57% had improved; the remaining 37% maintained stable disease activity. Analyses of other efficacy measures—patient and physician global assessments, disease activity score 28-joint erythrocyte sedimentation rate, and swollen and tender joint counts—demonstrated similar results: improvement was seen in 27–78% and worsening in 2–17%. No new safety signals emerged during the OLE. The adverse event profile among patients switching from adalimumab to sarilumab was consistent with the established safety profile of sarilumab. Conclusion: Among adalimumab CDAI partial responders who switched to sarilumab, there was a low likelihood of clinical worsening, while more than half of such patients achieved clinically meaningful improvement. Similar results were observed for other efficacy measures. This small risk of worsening coupled with the substantial likelihood of improvement after switch may help alleviate patients' concerns around loss of response and help inform shared decision-making. Acknowledgments: Study funding and medical writing support (Gregory Bezkorovainy, Adelphi Communications, New York) were provided by Sanofi Genzyme (Cambridge, USA) and Regeneron Pharmaceuticals, Inc. (Tarrytown, USA) in accordance with Good Publication Practice (GPP3) guidelines. Amy Praestgaard (Sanofi Genzyme employee) contributed to the statistical analysis for this abstract. Disclosure of Interests: Jeffrey Curtis Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Corrona, Janssen, Lilly, Myriad, Pfizer, Regeneron, Roche, UCB, Consultant of: AbbVie, Amgen, Bristol-Myers Squibb, Corrona, Janssen, Lilly, Myriad, Pfizer, Regeneron, Roche, UCB, Daniel Aletaha Grant/research support from: AbbVie, Novartis, Roche, Consultant of: AbbVie, Amgen, Celgene, Lilly, Medac, Merck, Novartis, Pfizer, Roche, Sandoz, Sanofi Genzyme, Speakers bureau: AbbVie, Celgene, Lilly, Merck, Novartis, Pfizer, Sanofi Genzyme, UCB, Gerd Rüdiger Burmester Consultant of: AbbVie Inc, Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB Pharma, Speakers bureau: AbbVie Inc, Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB Pharma, Kerri Ford Shareholder of: Sanofi Genzyme, Employee of: Sanofi Genzyme, Hubert van Hoogstraten Shareholder of: Sanofi, Employee of: Sanofi, Henry Leher Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., Karthinathan Thangavelu Shareholder of: Sanofi Genzyme, Employee of: EMD Serono, Sanofi Genzyme, Vivian Bykerk: None declared